Service orientation: effectuating business model innovation - Nair, S.; Paulose, H.; Palacios, M.; Tafur, Javier (Routledge, 2013)
The research argues for the need to correctly identify and strengthen the core competencies of a firm, especially relevant in the service-oriented firm context where value creation requires resourceful and efficient provision of service. This study of 17 airlines from Asia, Europe, and Oceania reveals a picture of inconsistencies in the core competence strategy of airlines. It brings out the situation in which firms believe and project that they are service oriented, but fail to have the core competence strategies of a service firm or the business model innovations that lead to service orientation, thus leading to performance heterogeneity among intra-industry firms having similar business models. This paper proposes that seemingly similar business models differ in performance due to their service orientation and identification of the core competence serves as both the primary requirement for business model innovation and a measuring indicator of service orientation. The research on the airline industry advances the understanding of how core competence strategy and business model innovation constructs behave in the service firms' effort to gain sustainable competitive advantage.